Perceptions of a mobile phone-based approach to promote medication adherence: A cross-sectional application of the technology acceptance model - Bernard Appiah; Irene Akwo Kretchy; Aya Yoshikawa; Lucy Asamoah-Akuoko; Christopher R. France (Elsevier, 2021)
Background: In several African and Asian countries, callers to mobile phones sometimes hear a song or message in place of the typical ringing sound. This application, called caller tunes, may offer a unique opportunity to promote medication adherence that is yet to be explored. Objectives: Assess the application of the technology acceptance model to a potential caller tunes approach designed to enhance medication adherence, with a specific focus on the interrelationships of perceived ease of use, perceived usefulness, cost, and intention. Methods: Data from a cross-sectional sample of 996 adult mobile phone users in Ghana, approximately half of whom were current caller tunes users, was examined using exploratory factor analysis for scale evaluation and structural equation modeling to assess associations among perceived ease of use, perceived usefulness, and cost on intention to use mobile phone caller tunes to promote medication adherence. Results: Consistent with the technology acceptance model, intention to use the caller tunes as a means of enhancing medication adherence was higher among those who viewed the application positively in terms of ease of use and usefulness. Among those who were already caller tunes users, availability as a free download was also associated with more positive intentions. Conclusion: The present study provides preliminary evidence in support of caller tunes as a novel strategy to promote medication adherence. Future studies interested in using this approach would be advised to consider factors such as participants' current use of caller tunes, age, availability as a free download, and perceptions of ease of use and perceived usefulness of the approach as potential moderators of study outcomes.